Characterizing outdoor air using microbial volatile organic compounds (MVOCs) - Garcia Alcega, Sonia; Coulon, Frederic (Apple Academic Press, 2018)
Exposure to bioaerosols containing airborne microorganisms and their by-products from outdoor environments such as industrial, urban or agricultural sites is of great concern as it is linked to adverse health effects in humans including respiratory diseases and infections. The risk exposure from outdoor emissions is difficult to quantify in real-time as the microbial concentration in air is low and varies depending on meteorological factors, anthropogenic activities, and sampling conditions. In addition, the collection of sufficient amount of sample to generate statistically distinguishable and reproducible patterns to characterize and quantify bioaerosols is still a challenge, and this analysis cannot be performed in real time yet. Microbial volatile organic compounds (MVOCs) can be used to chemically characterize ambient bioaerosols and identify pathogens early in air overcoming the inherent limitations of culturing. This book chapter aims to critically review the sampling techniques and analytical approaches that are currently available for the study of MVOCs from industrial, agricultural and rural emissions. Current challenges in MVOCs sample collection, analytical and speciation analysis are addressed, and recommendation for the implementation of a rapid, reproducible and sensitive analytical framework for fingerprinting bioaerosols is provided.